Stress analysis of an air tube bracket on a heavy-duty commercial vehicle’s chassis - (:unkn) unknown (My University, 2023)
This study is performed on the air tube bracket system of a heavy-duty commercial truck oscillating at its natural frequency under dynamic load exposed from all along its route. The dynamic analysis of the bracket with the entire commercial vehicle is made based on the data from rough road conditions. In all studies, the finite element models are created with the Medina software, and the solving process is performed with the Permas software. The results of the current work provided not only the optimum geometry of the air tube bracket system of a heavy-duty truck but also its ideal dimensions. The analysis also revealed that in addition to the geometry the straps’ width and their locations are of paramount importance in their overall performance.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Otomotiv Mühendisliği; Fizik Bilimleri; Makine Mühendisliği; Automotive Engineering; Physical Sciences; Mechanical Engineering; air tube bracket; finite element analysis; heavy-duty commercial vehicle; simulation; stress analysis